Pain, the Brain, and Osteoarthritis - Vinall, Maria (MD Conference Express, 2011)
Data appears to demonstrate that chronic pain imparts a specific signature on the brain that is associated with functional, behavioral, and chemical changes in the cerebral cortex. The specificity of this pain signature for different clinical conditions may provide the opportunity to develop targeted therapies for osteoarthritis and other chronic painful conditions.